2015
DOI: 10.3174/ajnr.a4496
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Significance of Cortical Superficial Siderosis for Alzheimer Disease in Patients with Cognitive Impairment

Abstract: BACKGROUND AND PURPOSE:Because the diagnostic significance of cortical superficial siderosis for Alzheimer disease and the association between cortical superficial siderosis and the topographic distribution of cerebral microbleeds have been unclear, we investigated the association between cortical superficial siderosis and clinicoradiologic characteristics of patients with cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 33 publications
2
12
0
2
Order By: Relevance
“…Previous data on cSS in large consecutive memory clinic series are relatively limited. Prevalence of cSS in memory clinic setting ranges from 2.1% to 6.1%, 5,13,14,25 in line with our prevalence of 3.0%, with a 0.7% prevalence in healthy populations. 26 cSS occurred in varying diagnoses throughout our series, with the highest prevalence observed in vascular dementia, followed by AD.…”
Section: Statistical Analysis Categorical Variables Were Analyzed Withsupporting
confidence: 89%
“…Previous data on cSS in large consecutive memory clinic series are relatively limited. Prevalence of cSS in memory clinic setting ranges from 2.1% to 6.1%, 5,13,14,25 in line with our prevalence of 3.0%, with a 0.7% prevalence in healthy populations. 26 cSS occurred in varying diagnoses throughout our series, with the highest prevalence observed in vascular dementia, followed by AD.…”
Section: Statistical Analysis Categorical Variables Were Analyzed Withsupporting
confidence: 89%
“…Fourteen studies (all published) met our predetermined criteria, however, five of these were from a same cohort, and other three were from cohorts of intracerebral hemorrhage (ICH) population. Finally, seven studies were pooled in a meta-analysis (Figure 1) (79, 1215). Characteristics of the included studies are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, few studies investigated the relationship between cSS and dementia, and the results are controversial. Zonneveld et al found a higher prevalence of cSS in patients with AD than those with mild cognitive impairment (MCI) (8), whereas a recent study failed to demonstrate the diagnostic significance of cSS for AD (9). We thus performed a meta-analysis to determine whether associations between cSS and dementia or AD exist in patients with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…6,32,33 Second, concomitant presence of CMB and cSS points toward a common underlying cause, as has been shown in CAA 34 and AD. 35 However, other studies found that CMB and cSS do not necessarily occur simultaneously in CAA. 19,20 Third, progression of CMB and cSS over time, as shown in adult patients with CAA, 29 points towards a common neuropathological mechanism.…”
Section: Our Findings Might Indicate Early Caa In Dsmentioning
confidence: 95%